Ars 06 : toden tuntu = sense of the real - KIASMA (Museum of Contemporary Art), Helsinki (Helsinki : KIASMA (Museum of Contemporary Art) Helsinki, 2006)
AES ; Borremans, Michaël ; De Bruyckere, Berlinde ; Castro, Jota ; Chapman, Dinos & Jake ; Coyne, Petah ; Cutler, Amy ; Doherty, Willie ; Echavarria, Juan Manuel ; El Perro ; Filomeno, Angelo ; Fridkes, Vladimir ; Hausswolff, Carl Michael von ; Henricksen, Kent ; IC-98 ; Just, Jesper ; Kalleinen, Tellervo ; Kobayashi, Naoto ; Kochta-Kalleinen, Oliver ; Kraijer, Juul ; Lenzlinger, Jörg ; Levé, Édouard ; Martin, Walter ; Muñoz, Paloma ; Muntean & Rosenblum ; Neudecker, Mariele ; Nguyen-Hatsushiba, Jun ; Nilsson, Lars ; Nordanstad, Thomas ; Odani, Motohiko ; Philipsz, Susan ; Piene, Chloe ; Ponomarev, Alexander ; Raidpere, Mark ; Sandison, Charles ; Shu-min Lin ; Sosnowska, Monika ; Steiner, Gerda ; Tabaimo ; Toemsombat, Montri ; Vaara, Roi ; Varejao, Adriana ; Vasiliev, Yuri ; Vega, Sergio ; Wirkkala, Maaria ; Yamashita, Mai
Engels, Fins
Exhibition. ARS 06 : Sense of the Real. KIASMA (Museum of Contemporary Art) Helsinki. 2006-01-21. 2006-08-27
boek